Effect of bilateral FDI, energy consumption, CO2 emission and capital on economic growth of Asia countries. (November 2019) - Muhammad, Bashir; Khan, Sher
Abstract: The current study objective is to contribute to the factors that make better the economic growth of the Asia countries with an importance on the frequently deserted bilateral FDI, energy use, CO2 emissions and capital role in the economic growth. This study applies generalized method of moments (GMM), OLS regression, fixed effect and random effect estimators with cross countries data for 34 host countries of Asia and 115 source countries over the period 2001–2012. The empirical results demonstrated that energy consumption, FDI inflows and FDI outflows, CO2 emission and capital play important role in economic growth of Asia countries. The current study suggest that make better policies for the utilization of energy, use of clean energy and use appropriate and advanced technology for energy in Asia countries and also encourage foreigner investors to their countries and invest in other countries which will increase their economy because economic growth increases due to both FDI inflows and outflows, energy use, CO2 emission, and capital of host countries and source countries. Highlights: The study assesses effect of FDI, EC, CO2 and capital on economic growth in Asia. The study uses static and GMM estimators for 34 host and 115 source countries. The difference FDI, FDI inflows and FDI outflows enhance economic growth. The EC and CO2 of host and EC and capital of source countries boost economic growth. The difference EC and capital reduces economic growth of Asia Countries.